ASSESSMENT OF WOUND HEALING ACTIVITY OF POTENT HERBAL EXTRACTS GEL IN ALBINO WISTAR RAT - WAYAL, VIPUL; NV, THORAT (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The purpose of this study was to formulate and determine the wound healing activity of gel containing the blend of potent herbal extracts from various plants such as Curcuma longa L., Tridax procumbens L., and Jatropha curcas L. Methods: The crude extracts were obtained by the Soxhlet extraction and maceration method. Preliminary phytochemical screening was done for all extracts. Two different concentrations of extract gels (HF1 and HF2) were prepared using Carbopol 934 as a gel base. Prepared gels were further evaluated for different parameters such as appearance, pH, viscosity, spreadability, extrudability, skin irritation test, and stability studies. Excision wound model used to determine wound healing activity in albino Wistar rat. Animals were divided into four groups and each group contains six animals (n=6). Soframycin was used as a standard treatment. Prepared formulations were applied to wounds for all 14 days of study. Wound contraction rate was measured at specified day’s intervals during the study. Results: Preliminary phytochemical analysis confirmed the presence of the bioactive phytoconstituents. Both the gel formulations showed good gelling properties and homogeneity. The pH of both gels lies in the normal pH range of human skin and there is no skin irritation. Formulations were found within the specified limit in stability studies. The obtained results of wound contraction rate were higher in Group IV which was treated with HF2 gel formulation compared to the control group (*p<0.05). Conclusion: It was concluded that the prepared herbal gel formulation shows a promising wound healing effect compared to synthetic medicament.